Reduction of stent‐associated morbidity by minimizing stent material: a prospective, randomized, single‐blind superiority trial assessing a customized 'suture stent'. (15th December 2020) - Betschart, Patrick; Piller, Alberto; Zumstein, Valentin; Schmid, Hans‐Peter; Engeler, Daniel S.; Güsewell, Sabine; Pratsinis, Manolis; Abt, Dominik
Abstract : Objectives: To compare a customized 'suture stent' with a standard ureteric stent regarding stent‐related symptoms, safety and efficacy. Materials and Methods: Patients with urolithiasis located proximal to the iliac vessel crossing, requiring stenting in preparation for secondary ureterorenoscopy (URS) were randomized to standard ureteric stenting or a suture stent. Secondary ureterorenoscopy was performed 2–6 weeks later. The Ureteral Stent Symptoms Questionnaire (USSQ) was completed after 1 week, on the day before URS and 2–6 weeks after stent removal. Stent efficacy and safety were systematically assessed. Results: A total of 88 patients were included in the analysis. The median (range) suture stent length was 10 (5–25) cm vs 26 cm for standard stents. Operation time was longer for insertion of the suture stent (24.0 vs 14.5 min; P < 0.001). Patients with a suture stent had a significantly lower USSQ urinary symptoms score 1 week after stent insertion, adjusted for baseline symptoms by subtracting scores from the final visit without indwelling stent (mean 7.1 vs 13.7, difference −6.6, 95% confidence interval [CI] −3.4 to −9.8; P < 0.001). Prior to secondary URS (after 2–6 weeks), baseline‐adjusted urinary symptoms (mean 4.7 vs 12.2, difference −7.5, 95% CI −4.5 to −10.4; P < 0.001) and pain subscores (11.5 vs 17.6, difference −6.1, 95% CI −0.7 to −11.6; P = 0.004) were significantly lower in the suture stent group. All other USSQ subscores showed no significant differences. Adverse events occurred in 15 patients and were similarly frequent in the two groups. No significant differences were found between the groups regarding ureteric access during secondary URS. Conclusion: Replacement of the distal part of ureteric stents by a suture can reduce stent‐associated symptoms without restrictions regarding secondary stone removal or safety.